CEO Characteristics And Their Effect Towards Advanced Manufacturing Technology Adoption In Malaysian Small And Medium Scale Manufacturing Industries - Salehuddin, Ali Hikmat Mohamed (2000)
Government effort to bring Malaysia to a developed nation status results in an emphasis o~ the modernization of small and medium scale manufacturing industries. Generally, SMis are lagging behind in terms of embracing the latest manufacturing technology. CEOs of small and medium scale manufacturing industry maintain a near total control on the decision making and the operations of the firms. This research attempts to investigate the characteristics of CEOs' innovation mindset, flexibility, perseverance and risk taking propensity on the extent of adoption of advanced manufacturing technology, AMT.